Cryptic pocket formation underlies allosteric modulator selectivity at muscarinic GPCRs - Scott A. Hollingsworth (Nature Portfolio, 2019)
Allosteric GPCR modulators can achieve exquisite subtype selectivity, but the underlying mechanism is unclear. Using molecular dynamics simulations, the authors here identify a previously undetected dynamic pocket in muscarinic GPCRs that is critical for subtype selectivity of allosteric modulators.